Assessment of study among radiography students about how to take informed consent - Kushwaha, Vivodh; Singh, Shilpa (International Journal of Research in Medical Sciences, 2022)
Background: Consent form is an integral first step before any radiological procedure that engages methods that can be threatening to patients. Future radiographers i.e., radiography students should have sufficient and appropriate knowledge regarding obtaining an informed consent. The aim of my study is to evaluate and assess the knowledge and impart the importance of informed consent form among Radiography students under various conditions. Methods: A questionnaire based retrospective cross-sectional was used to assess the knowledge of informed consent among radiographic students. The study was carried out in radiology department of Maharishi Markandeshwar University. The questionnaire comprised of self-structured MCQs questionnaire consisted of demographic data and basic questions regarding informed consent. Results: Out of 156 undergraduate and postgraduate radiology paramedical students, 87 took part in the study. It was assessed how much information radiography students possess on taking informed consent. The gender ratio was allocated into 2 groups. First group was female consisting of 45 (51.72%) number of participants and second group male consisting of 42 (48.28%) number of students with mean of 21 years. Conclusions: Indulging on the subject of consent form, almost all of the students understood the concept of consent form or had heard about the concept of informed consent to some extent. Maximum students were in favour of classes being held discussing consent form. The statistical data of all participants who gave the correct answer is 81.20%, indicating that radiography students understand and grasp the concept of consent very well.